Analisa Kedip Tegangan Pada Sistem Distribusi Tenaga Listrik 20 KV Akibat Hubung Singkat Pada Penyulang Pedan 1 Klaten - Iksan, Venna Athyna Rahmatika, Ir. Jatmiko, M.T (2016)
PT. PLN (Persero) Rayon PEDAN is the power company that is engaged in the maintenance and distribution of electric power systems 20 kV in Pedan, Klaten. PT. PLN (Persero) Rayon PEDAN get electric power supply from 150/20 kV transformer which located in the GI / GITET PEDAN. In distribution system of electrical supplies often found a power interruptions that caused by short circuit. Short-circuit in the distribution system have occurred in a short time or expense resulting discontinuous nominal voltage drops while the so-called blink voltage. Short circuit which usually occur in the distribution system is short circuit to ground 1 phase, 2-phase and 3-phase. To determine the value of the pulsating voltage due to short circuit current calculation is necessary analysis and calculation of short circuit voltage blink per feeder length by 25%, 50%, 75% and 100%. Feeders are used for calculations and analysis is PEDAN feeder 1. Voltage Dip and percentage of voltage dip from nominal voltage during one phase to ground short circuit per long feeders 25%, 50%, 75% and 100% are 9635,253∠0,809° V in 48,176%; 7002,022∠0,914° V in 35,010%; 4202,695∠1,762° V in 21,014%; and 1372,800∠5,679° V in 6,864%. Voltage Dips and percentage of voltage dip from nominal voltage during 2 phases short-circuit per long feeders 25%, 50%, 75% and 100% are 21561,542∠0,001° V in 107,808%; 19674,550∠0,0001° V in 98,373%; 18076,717∠0,0003° V in 90,383%; and 17016,682∠0,0003° in 85,083%. Voltage Dip and percentage of voltage dip from nominal voltage during 3-phase short-circuit per long feeders 25%, 50%, 75% and 100% are 3609,572∠-66,724° V in 18.048%; 8100,636∠-71,503° V in 40.503%; 12980,559∠-70,193° V in 64.903%; and 17915,240∠-69,466° V in 89.576%.